Concept understanding and mathematical representation ability: DMR model with a reciprocal teaching approach - Indah Resti Ayuni Suri; Nanang Supriadi; Irma Yuliana; Suherman Suherman (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Understanding mathematical concepts and representations in mathematics learning is an understanding that needs to be mastered by students in order to show students in the learning process and solve various mathematical problems. In this article we report how MTs students in South Lampung Regency understand concepts and mathematical representations after being treated with DMR learning with a reciprocal teaching approach. This researcher used the Quasy Experimental Design research type with a 2x2 factorial design. The population of this study were MTs students in Central Lampung Regency with samples taken using Cluster Random sampling techniques totaling 60 students (experimental class n = 30 and control class n = 30). The instruments used to collect data were essay tests for understanding concepts and mathematical representations. The data analysis technique in this research is Multivariate Analysis of Variant (MANOVA) with a large significance value . Based on the calculations that have been carried out, the results show that the p-value of understanding concepts is 0.000 and mathematical representation is 0.000, so that the p-value of each understanding is less than 0.05, it can be concluded that there is an influence of the DMR learning model with reciprocal teaching on students' understanding of concepts and mathematical representations simultaneously or partially. The results of understanding mathematical representations were better than understanding concepts for the two learning treatments given.